Looking up and out: transcending techniques in counselling for grief and loss with philosophy - Stow, Dianne Margaret (Curtin University, 2013)
This thesis is a phenomenological study of heeding consciousness in lived experience. Narratives of the lives of counsellor and clients embrace vulnerability as courage to face death and loss. Through philosophy and literature, I disclose what is immanent in a counsellor’s life. I question traditional techniques and theories. I present grief and loss as ultimate situations in life, and reveal one other: being-as-counsellor is primarily being-self in genuine conversations, reverently holding human-hood in cupped hands.